Some new regularity criterion for MHD three-dimensional flow
The aim of the paper is to establish regularity criteria for the weak solution of fluid passing through the porous media in R^3. We show that if (grad_hu,_3b_3) belongs to L^2alpha,2gamma with 2/alpha+3/gamma<=3, 1<=gamma<=infinity, then the weak solution is regular and unique; if (grad_hu, grad_hb) belongs to L^2alpha,2gamma with 2/alpha+3/gamma